Targeting quality of life in asthmatic children: The MyTEP pilot randomized trial. (July 2019) - Montalbano, Laura; Ferrante, Giuliana; Cilluffo, Giovanna; Gentile, Manuel; Arrigo, Marco; La Guardia, Dario; Allegra, Mario; Malizia, Velia; Gagliardo, Rosalia Paola; Bonini, Matteo; La Grutta, Stefania
Abstract: Background: Quality of life (QoL) is an important outcome in the management of children with asthma. Mobile Health (m-Health) and Therapeutic Education Programs (TEPs) are increasingly recognized as essential components of pediatric asthma management to improve disease outcomes. Objective: To evaluate the effect of an education program (MyTherapeutic Education Program, MyTEP) that couples multidisciplinary TEP intervention with an m-Health Program (mHP) in improving QoL in asthmatic children. Methods: This single-center study employed a nonblinded randomized clinical trial design. Italian-speaking children (6–11 years) with mild-moderate asthma were eligible for participation. Participants were randomly paired 1:1 with a control group that received mHP (smartphone app) or an intervention group that received MyTEP (TEP plus a smartphone app). Patients were followed up for 3 months. Descriptive statistics, Least Square (LS) mean change and Generalized Linear Mixed model were used for analysis. Results: Fifty patients were enrolled. The Pediatric Asthma Quality of Life Questionnaire (PAQLQ) score improved in both MyTEP (p = 0.014) and mHP (p = 0.046) with the minimally clinically significant difference of ⩾0.5 points reached in 23% of MyTEP and in 16% of mHP. Changes in PAQLQ scores were significantly greater in MyTEP than in mHP (LS mean difference: 0.269 p = 0.05). PAQLQ score was: positively associated with MyTEP (p = 0.023) and study time (p = 0.002); and inversely associated with current passive smoke exposure (p = 0.003). Conclusion: Despite the small sample size and short observation period, this study demonstrated that implementing a multidisciplinary TEP with an m-Health program results in gains in QoL of children with asthma. Highlights: QoL significantly improved in MyTEP vs. m-HP group. Asthma control significantly improved only in MyTEP but no differences between groups were found in treatment adherence. A significant improvement in spirometry parameters was found in both the MyTEP and m-HP groups. QoL was associated with MyTEP; subjects currently exposed to passive smoke were those reporting a greater negative impact on their QoL.